Issuing Birth Certificates and ID Cards for Newborns Following a Surrogate Birth and the Legal and Ethical Responsibilities of the Medical Team - A Milanifar; MM Akhondi; Z Behjati Ardakani; A Abdolahzadeh (JRI, 2008)
Infertility is known as one of the major problems that raises serious concerns due to its influence on social and family ties. Therefore, infertile couples have to resort to all methods of reproduction to overcome the problem. Surrogacy is considered one of the assisted reproductive techniques involving the third party and it is recommended to some infertile couples. According to the Iranian Civil Law, physicians are assigned to issue the birth certifi-cate for the offspring of the woman who has delivered it, while issuing unreal birth certificates will undoubtedly bring about penal fines. Applying surrogacy and issuing birth certificates makes the law turn a blind eye to the matter in certain cases which contradicts physicians’ assigned duties in this regard. Considering what was mentioned above and with regards to the current problems which emphasize the urgent amendment of the law, the authors try to introduce a short-term solution to the problem. In this approach, the birth certificate along with other documents is recorded by the executive medical team to be used to issue an ID card for the child regarding his or her biological parents.
Keywords: Surrogate, Birth certificate, ID card, Civil responsibility